Peran Aplikasi DANA untuk Meningkatkan Kemudahan Transaksi Non Tunai - Azlina Wati; Samintan Samintan; Elly Nielwaty (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The development of digital technology has driven significant changes in people's transaction patterns, including the increased use of app-based financial services. This study aims to analyze the role of the DANA app in increasing the convenience of cashless transactions in Indonesia. The method used was a literature review, analyzing journals, reports, and official documents related to the use of digital wallets and the development of DANA services over the past three years. The results show that DANA contributes to accelerating transaction processes, increasing accessibility to financial services, and providing secure and efficient payment features. Features such as QRIS, flexible balance top-ups, instant transfers, and integration with various public and commercial services have proven to facilitate users' cashless transactions. However, challenges remain, including unequal digital literacy, data security risks, and network limitations in some regions. Overall, the DANA app plays a crucial role in accelerating the digital payment ecosystem and increasing transaction convenience for the Indonesian people.